Major vault protein regulates tumor-associated macrophage polarization through interaction with signal transducer and activator of transcription 6 - Yu, Chen; Zhu, Qingmei; Ma, Caijiao; Luo, Chuanjin; Nie, Longyu; Cai, Huanhuan; Wang, Qiming; Wang, Fubing; Ren, Hong; Yan, Huan; Xu, Ke; Zhou, Li; et al. (Frontiers in Immunology, 2024)
Tumor-associated macrophages (TAMs) are critical in the tumor microenvironment (TME) of hepatocellular carcinoma (HCC). Major vault protein (MVP) mediates multidrug resistance, cell growth and development, and viral immunity. However, the relationship between MVP and TAMs polarization has not been clarified in HCC. We found that MVP significantly increased M2-TAMs infiltration levels in tumor tissues of HCC patients. MVP promoted HCC proliferation, metastasis, and invasion by regulating M2 polarization in vivo and in vitro. Mechanistically, MVP associated with signal transducer and activator of transcription 6 (STAT6) and enhanced STAT6 phosphorylation. STAT6 translocated from the cytosol to the nucleus and regulated M2 macrophageassociated gene transcription. These findings suggest that MVP modulates the macrophage M2 transcriptional program, revealing its potential role in the TAMs of TME.